Rodzina w procesie konstruowania obrazu osób niepełnosprawnych. Rola płci w niepełnosprawności - Rudek, Iwona (Karkonoska Państwowa Szkoła Wyższa, 2012)
The author draws attention to the issue of gender in disability. The term “disabled person” turns out to be gender neutral. Women with disabilities consider themselves to be treated as a “third sex”. The discrimination of disabled women results from a lack of sensitivity to the sex of the disabled. This points out the need to change the attitudes towards people with disabilities in early childhood as well as the necessity to pay more attention to the gender of disabled children. Sex becomes a matter which is forgotten, perhaps even becoming irrelevant. Women and their function are pushed into the background, which results in the gender-related stereotyping of their social roles, a more difficult way of career advancement (the so-called “glass ceiling effect”), lower wages for women working in the same positionsas men, and the low participation of women in public life.
Keywords: rodzina; niepełnosprawni; płeć; społeczeństwo